DEVELOPMENT OF ETHNOSCIENCE INTEGRATED E-WORKSHEET IN ACID BASE MATERIALS TO IMPROVE CRITICAL THINKING SKILL - Indra Adia Kusuma; Woro Sumarni (EDUSAINS, 2024)
Critical thinking skills are one of the skills needed in the current era of education. The ability to think critically is an important key for students in successful problem solving. This research aims to develop an ethnoscience-integrated Electronic Student Worksheets (E-LKPD) for acid-base learning to enhance students' critical thinking skills. The Research & Development (R&D) 4-D model, developed by Thiagarajan, was utilized. The research subjects were 11th-grade students of Science at SMAN 1 Cigugur, in the academic year 2022/2023. The E-LKPD was designed in HTML 5 format, accessible online through smartphones and laptops. The material presentation in the introductory activities was contextual, incorporating ethnoscience content related to local phenomena, enabling students to understand and explore the connection between these phenomena and acid-base concepts. The validation results by expert validators showed a high validity rate of 92%. The assessment of student responses through questionnaires yielded scores of 87.2% in the small-scale trial and 89.4% in the large-scale trial, indicating that the E-LKPD was highly practical. To evaluate the effectiveness of the ethnoscience-integrated E-LKPD in enhancing critical thinking skills, pre-tests and post-tests were conducted. The N-gain value of 0.71 indicated a high improvement in students' critical thinking skills. The findings demonstrate that the developed E-LKPD integrated with ethnoscience effectively enhances students' critical thinking abilities. This is because the Ethnoscience Integrated E-LKPD media can connect learning in the classroom with the real experiences of students in everyday life, so that it can help students to develop critical thinking skills in the process.